Tissue investments related to water absorption and retention in Bromeliaceae: exploring variations in CAM metabolism expressing between dry and rainy seasons - Ana Laura Torrano Costa; Denis Coelho de Oliveira; Bruno Garcia Ferreira; Ana Silvia Franco Pinheiro Moreira (Rodriguésia)
Abstract Structure and function are strongly related in bromeliad leaves. Some species do not develop tank rosettes and must rely on other structural and physiological attributes to deal with environmental stressors. Three species of Bromeliaceae without tanks were compared according to their leaf structure (anatomy and pectin composition), water retention abilities, and photosynthetic pathway expressions. Tillandsia stricta is an epiphyte, shaded by the canopy in a riparian forest, T. usneoides occurs on palm trees in an adjacent opened area, while Dyckia minarum is terrestrial and exposed to high light intensities in rupestrian fields. Despite limiting light and/or water conditions in each habitat, these species occur in adjacent areas. While they express CAM metabolism, D. minarum demonstrated more expressive acidity. Its greater investments in tissues related to water absorption and retention may reflect its high exposure to sunlight, poor nutrient availability for growth, and CAM expression. Tillandsia usneoides modifies its water-storing capacity between seasons, a property possibly associated with the presence of high methyl-esterified HGs in its cell walls. The higher succulence and relative water content during the rainy season may stimulate photosynthetic activity and maximize CAM expression.